Approaching a complete repository of sequence-verified protein-encoding clones for Saccharomyces cerevisiae - Hu, Yanhui; Rolfs, Andreas; Bhullar, Bhupinder; Murthy, Tellamraju V. S.; Zhu, Cong; Berger, Michael F.; Camargo, Anamaria A.; Kelley, Fontina; McCarron, Seamus; Jepson, Daniel; Richardson, Aaron; Raphael, Jacob; et al.

(untitled) (Genome Research, 2007)
The availability of an annotated genome sequence for the yeast Saccharomyces cerevisiae has made possible the proteome-scale study of protein function and protein–protein interactions. These studies rely on availability of cloned open reading frame (ORF) collections that can be used for cell-free or cell-based protein expression. Several yeast ORF collections are available, but their use and data interpretation can be hindered by reliance on now out-of-date annotations, the inflexible presence of N- or C-terminal tags, and/or the unknown presence of mutations introduced during the cloning process. High-throughput biochemical and genetic analyses would benefit from a “gold standard” (fully sequence-verified, high-quality) ORF collection, which allows for high confidence in and reproducibility of experimental results. Here, we describe Yeast FLEXGene, a S. cerevisiae protein-coding clone collection that covers over 5000 predicted protein-coding sequences. The clone set covers 87% of the current S. cerevisiae genome annotation and includes full sequencing of each ORF insert. Availability of this collection makes possible a wide variety of studies from purified proteins to mutation suppression analysis, which should contribute to a global understanding of yeast protein function.